Supercritical Carbon Dioxide Drying of Methanol-Zinc Borate Mixtures - Gönen, Mehmet; Balköse, Devrim; Balköse, Devrim; Gupta, Ram B.; Ülkü, Semra; Ülkü, Semra (American Chemical Society, 2009)
Supercritical carbon dioxide (CO 2) drying of zinc borate species was investigated to evaluate possible chemical alterations in the product during the drying. Methanol-wetted zinc borates produced either from borax decahydrate and zinc nitrate hexahydrate (2ZnO · 3B 2O 3 ·7H 2O) or from zinc oxide and boric acid (2ZnO · 3B 2O 3 ·3H 2O) were dried by both conventional and supercritical carbon dioxide drying methods. Zinc borate samples dried by both techniques were characterized using analytical titration, X-ray powder diffraction (XRD), thermo gravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, elemental analysis, and scanning electron microscopy (SEM). It was found that while zinc borate obtained from zinc oxide and boric acid did not have any chemical interaction with CO 2, carbonates were formed on the surface of zinc borate obtained from borax decahydrate and zinc nitrate hexahydrate. The main factor for the carbonate formation during supercritical CO 2 drying is anticipated as the structural differences of zinc borate species. CO 2 is a nonpolar solvent, and it does not usually react with polar substances unless water is present in the medium. While 2ZnO · 3B 2O 3 ·3H 2O had three bound OH groups, 2ZnO · 3B 2O 3 ·7H 2O had five bound OH groups and one mole of water of crystallization. It is proposed that the water of crystallization reacts with CO 2 forming carbonic acid. Then, carbonic acid, which is stronger than boric acid, substitutes borate ions from their zinc salts.
Keywords: Zinc; Borate minerals; Carbonate formations; Chemical alteration; Water of crystallization